Evaluasi dan Perancangan Model Bisnis UMKM Miss Bluder dengan Business Model Canvas - Maharani Lingga Yasmin; Farda Hasun; Budi Sulistyo (MES Management Journal, 2024)
Miss Bluder is an MSME that sells bluder bread in the city of Bandung. In recent times, Miss Bluder has experienced a significant decline in sales. This is due to limitations in human resource management, suboptimal partnerships, and lack of effectiveness in the sales media used. This research aims to evaluate and design a new business model for Miss Bluder using the Business Model Canvas method. The data used included current business models, customer profiles from interviews, as well as business environment data from literature studies and online research. A SWOT analysis was carried out to formulate an improvement strategy, followed by the design of a Value Proposition Canvas, Channels, and Customer Relationships. After the business model design is completed, verification, financial simulation, and validation processes are carried out through evaluations and interviews with business owners. With the implementation of the new business model, it is hoped that Miss Bluder can overcome the decline in sales, improve business performance, and strengthen its position in the market.